Tourist Experience in Bromo Tengger Semeru National Park - Sean Albert Susanto; I Dewa Gde Satrya (AIBPM Publisher, 2023)
The development of Bromo Tengger Semeru National Park (BTSNP) can be done by looking at the tourism experience of Generation Z. The subject of this research is Generation Z (Gen Z). The main problem in this investigate is how the involvement of Gen Z traveling in BTSNP. This study points to describe the experience of Gen Z tourists in BTSNP. This investigate was conducted employing a subjective approach with information collection strategies, specifically interviews and writing. The conclusion of this study is BTSNP has succeeded in fulfilling tourist experience and tourist satisfaction for Gen Z tourists. The value of the research conducted is to identify the needs and experiences of Gen Z tourists as a market for the present and the future of tourism. Keywords: Tourist experience, tourist satisfaction, Gen Z